Prolonged cooling of andesitic-dacitic lava flows produces optimal groundmass material for 40Ar/39Ar dating - Chris E. Conway; Andrew T. Calvert; Osamu Ishizuka; Seiko Yamasaki; Isoji Miyagi; Yumiko Harigane; Graham S. Leonard (Chemical Geology, 2026)

Reply to comments on “Subsurface distribution of granites and greenstones in the Paleoarchean East Pilbara Terrane from 3-D gravity inversion” of Hayward et al. (2024) - Nathan Hayward; Andrew J. Calvert; Huaiyu Yuan; Klaus Gessner; Michael P. Doublier (Precambrian Research, 2024)

Seismic and Potential Field Constraints on Upper Crustal Architecture of Inner Bering Shelf, Offshore Southwestern Alaska - Rajesh Vayavur; Andrew J. Calvert (Tectonophysics, 2024)

Subsurface distribution of granites and greenstones in the Paleoarchean East Pilbara Terrane from 3-D gravity inversion - Nathan Hayward; Andrew J. Calvert; Huaiyu Yuan; Klaus Gessner; Michael P. Doublier (Precambrian Research, 2024)

Paleomagnetically defined brief lifespans for two large shield volcanoes in the Cascades Arc - Anthony F. Pivarunas; Dawnika L. Blatter; L.J. Patrick Muffler; Michael A. Clynne; Andrew T. Calvert; Lauren N. Harrison; Robert L. Christiansen (Journal of Volcanology and Geothermal Research, 2023)

Precaldera Mafic Magmatism at Long Valley, California: Magma-Tectonic Siting and Incubation of the Great Rhyolite System - Wes Hildreth; Judy Fierstein; Andrew T. Calvert (Journal of Volcanology and Geothermal Research, 2023)

Temporal relationship between the Lassen volcanic center and mafic regional volcanism - Aurelie Germa; Chris Perry; Xavier Quidelleur; Andrew Calvert; Michael Clynne; Charles B. Connor; Laura J. Connor; Rocco Malservisi; Sylvain Charbonnier (Bulletin of Volcanology, 2019)

Timescales of magmatic differentiation from alkali basalt to trachyte within the Harrat Rahat volcanic field, Kingdom of Saudi Arabia - Mark E. Stelten; Drew T. Downs; Hannah R. Dietterich; Gail A. Mahood; Andrew T. Calvert; Thomas W. Sisson; Hani Zahran; Jamal Shawali (Contributions to Mineralogy and Petrology, 2018)

Projected sea level rise and changes in extreme storm surge and wave events during the 21st century in the region of Singapore - Heather Cannaby; Matthew D. Palmer; Tom Howard; Lucy Bricheno; Daley Calvert; Justin Krijnen; Richard Wood; Jonathan Tinker; Chris Bunney; James Harle; Andrew Saulter; Clare O'Neill; et al. (Ocean Science, 2016)
Singapore is an island state with considerable population, industries, commerce and transport located in coastal areas at elevations less than 2 m making it vulnerable to sea level rise. Mitigation against future inundation events requires a quantitative assessment of risk. To address this need, regional projections of changes in (i) long-term mean sea level and (ii) the frequency of extreme storm surge and wave events have been combined to explore potential changes to coastal flood risk over the 21st century. Local changes in time-mean sea level were evaluated using the process-based climate model data and methods presented in the United Nations Intergovernmental Panel on Climate Change Fifth Assessment Report (IPCC AR5). Regional surge and wave solutions extending from 1980 to 2100 were generated using ∼ 12 km resolution surge (Nucleus for European Modelling of the Ocean – NEMO) and wave (WaveWatchIII) models. Ocean simulations were forced by output from a selection of four downscaled ( ∼ 12 km resolution) atmospheric models, forced at the lateral boundaries by global climate model simulations generated for the IPCC AR5. Long-term trends in skew surge and significant wave height were then assessed using a generalised extreme value model, fit to the largest modelled events each year. An additional atmospheric solution downscaled from the ERA-Interim global reanalysis was used to force historical ocean model simulations extending from 1980 to 2010, enabling a quantitative assessment of model skill. Simulated historical sea-surface height and significant wave height time series were compared to tide gauge data and satellite altimetry data, respectively. Central estimates of the long-term mean sea level rise at Singapore by 2100 were projected to be 0.52 m (0.74 m) under the Representative Concentration Pathway (RCP)4.5 (8.5) scenarios. Trends in surge and significant wave height 2-year return levels were found to be statistically insignificant and/or physically very small under the more severe RCP8.5 scenario. We conclude that changes to long-term mean sea level constitute the dominant signal of change to the projected inundation risk for Singapore during the 21st century. We note that the largest recorded surge residual in the Singapore Strait of ∼ 84 cm lies between the central and upper estimates of sea level rise by 2100, highlighting the vulnerability of the region.

High-resolution 40Ar/39Ar study of Mount Avital, northern Golan: reconstructing the interaction between volcanism and a drainage system and their impact on eruptive styles - Yishai Weinstein; Ram Weinberger; Andrew Calvert (Bulletin of Volcanology, 2013)

Age, geochemical composition, and distribution of Oligocene ignimbrites in the northern Sierra Nevada, California: implications for landscape morphology, elevation, and drainage divide geography of the Nevadaplano - Elizabeth J. Cassel; Andrew T. Calvert; Stephan A. Graham (International Geology Review, 2009)

Postshield stage transitional volcanism on Mahukona Volcano, Hawaii - David A. Clague; Andrew T. Calvert (Bulletin of Volcanology, 2009)

40Ar/39Ar ages of the AD 79 eruption of Vesuvius, Italy - Marvin Lanphere; Duane Champion; Leone Melluso; Vincenzo Morra; Annamaria Perrotta; Claudio Scarpati; Dario Tedesco; Andrew Calvert (Bulletin of Volcanology, 2006)